Autonomous vehicles and cycling: Policy implications and management issues. (September 2020) - Pettigrew, Simone; Nelson, John D.; Norman, Richard
Abstract: Cycling as a form of active transport has great benefits for individuals and society, yet prevalence rates in many countries are low. The advent of autonomous vehicles (AVs) is likely to have substantial implications for cyclists, however little is known about the nature and magnitude of the likely impacts and the resulting implications for government planning and policy. The aim of this exploratory study was to consult with a range of stakeholder groups to identify relevant issues and stimulate debate about future efforts to maximize the benefits of vehicle autonomy for cycling outcomes. Interviews were conducted with key stakeholders representing government (local, state, and federal departments responsible for transport, health, and/or infrastructure), cycling organizations, technology firms, AV manufacturing/servicing companies, trade unions, the law, insurers (public and private), transport policy consortia, and academia. The results suggest that AVs have the potential to increase cycling prevalence while reducing cycling accidents, but that a range of issues will need to be addressed to optimize these outcomes. In particular, informed decisions need to be made about the infrastructure and equipment investments that could encourage larger numbers of commuters to select cycling as their primary form of transport. Highlights: Autonomous vehicles have the potential to increase cycling rates The optimal form of road sharing between autonomous vehicles and bikes is unknown Roads may need to be modified to facilitate efficient road-sharing between modes Cyclists need encouragement to use relevant communication equipment and practices